Interleukin-6 is elevated in synovial fluid of patients with focal cartilage defects and stimulates cartilage matrix production in an in vitro regeneration model - Tsuchida, Anika I (BioMed Central, 2012)
INTRODUCTION: This study aimed to determine whether, as in osteoarthritis, increased levels of interleukin-6 (IL-6) are present in the synovial fluid of patients with symptomatic cartilage defects and whether this IL-6 affects cartilage regeneration as well as the cartilage in the degenerated knee. METHODS: IL-6 concentrations were determined by ELISA in synovial fluid and in conditioned media of chondrocytes regenerating cartilage. Chondrocytes were obtained from donors with symptomatic cartilage defects, healthy and osteoarthritic donors. The effect of IL-6 on cartilage regeneration and on metabolism of the resident cartilage in the knee was studied by both inhibition of endogenous IL-6 and addition of IL-6, in a regeneration model and in osteoarthritic explants in the presence of synovial fluid, respectively. Readout parameters were DNA and glycosaminoglycan (GAG) content and release. Differences between controls and IL-6 blocked or supplemented samples were determined by univariate analysis of variance using a randomized block design. RESULTS: Synovial fluid of patients with symptomatic cartilage defects contained more IL-6 than synovial fluid of healthy donors (P = 0.001) and did not differ from osteoarthritic donors. IL-6 production of osteoarthritic chondrocytes during cartilage regeneration was higher than that of healthy and defect chondrocytes (P < 0.001). Adding IL-6 increased GAG production by healthy chondrocytes and decreased GAG release by osteoarthritic chondrocytes (P < 0.05). Inhibition of IL-6 present in osteoarthritic synovial fluid showed a trend towards decreased GAG content of the explants (P = 0.06). CONCLUSIONS: Our results support a modest anabolic role for IL-6 in cartilage matrix production. Targeting multiple cytokines, including IL-6, may be effective in improving cartilage repair in symptomatic cartilage defects and osteoarthritis.